Peranan Wisdom terhadap Subjective Well-Being pada Dewasa Awal - Zahra Frida Intani; Aisah Indati (Gadjah Mada Journal of Psychology (GamaJoP), 2017)
Subjective well-being is one of the topics of positive psychology studies related to one’s quality of life, while wisdom is the highest ability that one can have from their life experiences. This study aimed to determine the contribution of wisdom on subjective well-being in early adulthood. The hypothesis proposed in this study was wisdom contributes positively toward subjective well-being in early adulthood. Participants of the study (N = 158) were undergraduate students (female = 98, male = 60) who are working on their final project (thesis). Data was collected using Skala Kesejahteraan Subjektif developed by Utami and the adaptation of The Three Dimensional Wisdom Scale (3D-WS). The result showed that wisdom significantly predicted subjective well-being in a positive direction.